P-30 Love your local hospice – a collaboration for the future. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Clarke, Elizabeth; Smith, Laura; Parkes, Diane
Abstract : In February 2016, 16 West Midlands adult and children's hospices joined forces to launch an advertising campaign to raise awareness, dispel myths and encourage our communities to Love Your Local Hospice. Community engagement was the key focus, and based on learning from the North West Hospice TV campaign we decided to focus on general awareness-raising rather than fundraising. Individual goals were put aside to achieve the joint ambition of reaching a wider audience. The agreed common themes were care, family, love, life, friendship, and being there for the whole community whenever they need us. The overarching objective was that all hospices were buying into a longer-term sustainable collaboration. The TV advert aired for 10 days on ITV and reached almost 1.5 million people across the region. It also ran for one month via ITV on Demand with a click through rate of 1.66% (double the normal rate) reaching over 90, 000 people. To support the advert a website was created with links to all individual hospices. A social media campaign also ran alongside utilising bespoke films for each hospice. This joint activity had an additional reach of over 300, 000 people. Hospices also ran their own events and activities to align with the campaign. The campaign achieved over 35 pieces of media coverage and was featured on Midlands Today and local radio. The success of the campaign has meant the cohesive effort continues with plans underway for a second awareness campaign in October followed by a joint income generation campaign scheduled for 2017. The Love Your Local Hospice model has been developed so that other hospices can benefit by investing into the campaign content at a reduced cost rather than setting such a campaign up from scratch. In conclusion the campaign demonstrated that a collective voice is stronger than one.